Comparison of total amino acid composition and total protein content in five wild mushrooms - Halyna Kopylchuk; Oksana Voloshchuk; Mariia Pasailiuk; Nina Fontana (Italian Journal of Mycology)
We studied the total amino acid compositions and total protein content in five wild mushrooms – Artomyces pyxidatus, Caloboletus calopus, Hericium flagellum, Strobilomyces strobilaceus, Xerocomellus porosporus. The highest total protein content is found in Xerocomellus porosporus (44.8% w/w) and Strobilomyces strobilaceus (42% w/w). In the fruiting bodies of the mushrooms, Hericium flagellum and Artomyces pyxidatus, the total protein content was the lowest, at 14.02% w/w and 17.7% w/w, respectively. The proportion of essential amino acids in the mushrooms was 42.26%, 44.98%, 46.99%, 39.33% and 40.97% in Xerocomellus porosporus, Caloboletus calopus, Strobilomyces strobilaceus, Artomyces pyxidatus, and Hericium flagellum, respectively. The proportion of hydrophobic amino acids ranged from 39.49% in Xerocomellus porosporus to 59.02% in Hericium flagellum. Therefore, the basidiomata of X. porosporus and S. strobilaceus are recommended as sources of protein, including essential amino acids, for the development of dietary supplements.